Efeitos de nanodoses do inseticida tiametoxam para a abelha Melipona scutellaris Latreille, 1811 (Hymenoptera, Apidae): da absorção ao orgão alvo - Grella, Tatiane Caroline (2017)
The Brazilian bees are responsible for pollinating about 40-90% of native plants according to the ecosystem. Among the species found in Brazil is Melipona scutellaris, eussocial, able to perform pollination by vibration. However, bee populations have been affected by the use of pesticides, such as thiamethoxam, a neonicotinoid and systemic insecticide, that is, its target organ is the brain and it can reach nectar and pollen through the sap of the plant. When the resources are ingested, the active ingredient first comes into contact with the intestine, the organ responsible for digestion and absorption, and then passes into the hemolymph, reaching the Malpighi tubules responsible for their filtration and excretion, as well as the brain, organ target. Due to the importance of understanding the metabolic pathway of this compound, the objective of this work was to evaluate the effects of nanodoses of the insecticide thiamethoxam in the intestine, Malpighi tubules and the brain of M. scutellaris forages. For this, the bees were collected directly from the colonies and exposed, orally, to sublethal doses of thiamethoxam, LC50 = 0.0453 ng i.a./μL diet; LC50 / 10 = 0.00453 ng i.a./μL diet and LC50 / 100 = 0.000453 ng i.a./μL diet. Then, they were dissected after the start of the exposure times, 1, 4, 8 and 24h, and subjected to the Hematoxylin and Eosin (HE), HSP90 (Thermal Shock Protein) and Tunel (Cell Death Detection Kit) techniques. Through the HE technique it was possible to observe that the higher concentrations caused alterations in the cellular morphology in the three studied organs, such as increased cellular elimination, strongly stained nuclei, loss of cytoplasmic material and chromatin condensation. The HSP90 technique showed an increase in the expression of the heat shock protein according to the increase in concentration at certain times and a balance in its production between the three organs, that is, when the production increases in one organ it decreases in the Other, except for the analysis of the results for the highest concentration, of the longer time in the target organ, which suffered a fall, which may indicate cellular death, which was not evidenced by the Tunel technique in any organ. Thus, we conclude that nanodoses of the insecticide thiamethoxam cause morphological damage, increase the expression of heat shock proteins and can lead to death